Make nature's role visible to achieve the SDGs. (22nd April 2022) - Hole, David G.; Collins, Pamela; Tesfaw, Anteneh; Barrera, Lina; Mascia, Michael B.; Turner, Will R.
Abstract : Non-technical summary: Implicit in the UN's Sustainable Development Goal (SDG) Agenda is the notion that environmental sustainability is intertwined with, and underpins, the 17 Goals. Yet the language of the Goals, and their Targets and indicators is blind to the myriad ways in which nature supports people's health and wealth – which we argue represents a key impediment to progress. Using examples of nature–human wellbeing linkages, we assess the language of all 169 Targets to identify urgent research, policy, and action needed to spotlight and leverage nature's foundational role, to help enable truly sustainable development for all. Technical summary: Nature's foundational role in helping achieve the SDGs is implicit rather than explicit in the language of SDGs Goals, Targets, and indicators. Drawing from the scientific literature describing how nature underpins human wellbeing, we carry out a systematic assessment of the language of all 169 Targets, categorizing which Targets are dependent upon nature for their achievement, could harm nature if attained through business-as-usual actions, or may synergistically benefit nature through their attainment. We find that half are dependent upon nature for their achievement – yet for more than two-thirds of those nature's role goes unstated and risks being downplayed or ignored. Moreover, while achieving the overwhelming majority of the 169 Targets could potentially benefit nature, more than 60% are likely to deliver 'mixed outcomes' – benefitting or harming nature depending on how they're achieved. Furthermore, of the 241 official indicators <5% track nature's role in achieving the parent Target. Our analysis provides insights important for increasing effectiveness across the SDG agenda regarding where to invest, how to enhance synergies and limit unanticipated impacts, and how to measure success. It also suggests a path for integrating the 'nature that people need' to achieve the SDGs into the CBD's post-2020 Global Biodiversity Framework. Social media summary: Harmonizing links between the SDGs and the CBD's post-2020 Global Biodiversity Framework is vital for promoting sustainable development